The Legal Interpretation: Proposals for its Application in Tax Law - Donayre Lobo, Gabriel (2014)
The first half of this report contains the concept of interpretation and its relationship with the written language. In addition, it proposes how the ambiguity of the language is one of the main problems for legal interpretation. The second half of this report establishes which components of the legal interpretation are, from a theoretical perspective –according to doctrine and practice– following jurisprudence, criteria and methods of interpretation allowed in Law. This part also proposes a route for the legal interpretation in Tax Law. The third part of this report contains the interpretation of two resolutions from the Tax Court following the described route.